Democracy and elections in Africa - Lindberg, Staffan I. (Baltimore Johns Hopkins University Press, 1969)
This volume studies elections as a core institution of liberal democracy in the context of newly democratizing countries. Political scientist Staffan I. Lindberg gathers data from every nationally contested election in Africa from 1989 to 2003, covering 232 elections in 44 countries. He argues that democratizing nations learn to become democratic through repeated democratic behavior, even if their elections are often flawed.
Includes index
Keywords: Elections--Africa.